The effect of including increased arterial stiffness in the upper body when modelling Coarctation of the Aorta. Issue 5 (4th April 2019) - Pathirana, Dilan; Johnston, Barbara; Johnston, Peter
Abstract: Coarctation of the Aorta is a congenital narrowing of the aorta and diagnosis can be difficult. Treatments result in idiopathic sequelae including hypertension. Untreated patients are known to develop increased arterial stiffness in the upper body, which worsens with time. We present results from simulations with a one-dimensional mathematical model, about the effect of stiffness, stenting, surgery and coarctation severity on blood pressure, Pulsatility and Resistivity Index. One conclusion is that increased stiffness may explain both hypertension in treated patients and why diagnosis can be difficult.